Chinese herbal medicine combined with western medicine for the treatment of type 2 diabetes mellitus with hyperuricemia: A systematic review and meta-analysis - Hongyan Liu; Sihan Peng; Haipo Yuan; Yuchi He; Jiao Tang; Xiyu Zhang (Frontiers Media S.A., 2023)
Background: Chinese herbal medicine (CHM) has the advantage of being safe and effective and has been widely used in clinical practice for the treatment of type 2 diabetes mellitus (T2DM) with hyperuricemia (HUA), but its overall efficacy and safety remain unclear. This study aimed to evaluate the efficacy and safety of CHM for the treatment of T2DM with HUA based on randomized controlled trials (RCTs) to provide clinical evidence.Methods: The protocol evaluated in this study is registered with PROSPERO (CRD42022351519). As of November 2022, eight databases were searched, and RCTs of CHM for the treatment of T2DM with HUA were included. Outcome indicators observed included fasting blood glucose (FBG), 2-h postprandial glucose (2hPG), glycated hemoglobin (HbA1c), uric acid (UA), triglycerides (TG), total cholesterol (TC), overall effectiveness, and adverse events. Utilizing Review Manager 5.4, Stata V14.0, and GRADEpro, the included studies were evaluated, and the quality of the evidence was determined.Results: 18 RCTs covering 1,311 patients were included in this study. The results of the study demonstrated that the combination of CHM and western medicine (WM) was more effective in treating patients with T2DM with HUA than WM alone, with significant improvements in FBG (weighted mean differences (WMD) = −0.60.95% confidence interval (CI) [−0.81, −0.40], p < 0.00001), 2hPG (WMD = −1.12.95% CI [−1.64, −0.60], p < 0.0001), HbA1c (WMD = −0.80.95% CI [−1.04, −0.56], p < 0.00001), UA (WMD = −53.47.95% CI [−67.45, −39.48], p < 0.00001), TG (WMD = −0.56.95% CI [−0.74, −0.38], p < 0.00001), TC (WMD = −0.49.95% CI [−0.65, −0.33], p < 0.00001), and overall effective rate (risk ratio (RR) = 1.29.95%CI [1.13, 1.48], p = 0.0002). The quality of evidence for all outcomes was low.Conclusion: Compared with WM alone, the combination of CHM and WM was more effective in treating patients with T2DM with HUA, with significant improvements in glucose metabolism, uric acid, and lipids. However, further evaluation by high−quality RCT results is needed due to the low quality and high heterogeneity of the evidence.Systematic Review Registration: [https://systematicreview.gov/], identifier [CRD42022351519].